Evaluation of oat germplasm for resistance to Fusarium Head Blight. - Gagkaeva , T.; Gavrilova , O.; Yli-Mattila, T.; Loskutov , I. (Plant Breeding and Seed Science, 2011)
The objectives of this study were to screen the VIR Avena germplasm collection for Fusarium head blight (FHB) resistance and to identify the resistant oat genotypes by using the different scoring of the disease. After artificial inoculation harvested grain samples were assays on the combination of three parameters: percentage of Fusarium damaged kernels (FDK), DNA of trichothecene-producing Fusarium fungi and mycotoxin accumulation. The clear correlation between the parameters for every individual genotype was not detected. The results support the several components of resistance to Fusarium head blight in oats (invasion, spreading and mycotoxin accumulation), which are controlled by different genetic systems. The hull-less genotypes consid- ered to be more resistant in the Avena germplasm. Seven landraces genotypes and five cultivars originated from Asian region and two cultivars originated from European region seem to be suitable genetic resources for resistance to FHB.